Perceptions and experiences of informal street traders on Covid-19 and its effect on sales and revenue in Pretoria - Maphutha, Thakgalo Magauwane (University of the Witwatersrand, Johannesburg, 2023)
The Covid-19 restrictions and strategies imposed in order to reduce the spread of the virus had dire consequences on the sales and livelihood of both the formal and informal sectors. The lockdown made it challenging for small and big businesses to operate as per normal, which included informal street traders. This study intended to find out the perceptions and views of informal street traders with the focus on their sales and revenue during Covid-19 lockdown. The research was designed as a phenomenological study as it was concerned with understanding the effects of Covid- 19 through the in-depth experiences of informal street traders. The study adopted a qualitative research design, with face-to-face interviews as the primary data collection method. In addition, previously published studies were reviewed as part of the secondary literature review. This study had a sample of 30 informal street traders from Pretoria working along Church Street. A key discovery in this study is that like many sectors, informal street traders were hit very hard by the pandemic, more especially during the lockdowns. The sales and revenue of informal street traders decreased drastically, leaving the participants with challenges that will take years to overcome. Most informal street traders participate in the sector as their primary source of income due to a lack of opportunities in the country and are the main breadwinners. To many, Covid-19 added to the already existing day-to-day challenges. Regardless of the significance of informal street trading, the government failed to provide them with any assistance to curb the negative impact of the pandemic on their livelihood
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Covid-19; street traders; informal sector; government assistance; SDG-8: Decent work and economic growth